Experimental helium‐beam radiography with a high‐energy beam: Water‐equivalent thickness calibration and first image‐quality results. Issue 8 (20th June 2022) - Knobloch, C.; Metzner, M.; Kehrein, F.; Schömers, C.; Scheloske, S.; Brons, S.; Hermann, R.; Peters, A.; Jäkel, O.; Martišíková, M.; Gehrke, T.
Abstract: Purpose: A clinical implementation of ion‐beam radiography (iRad ) is envisaged to provide a method for on‐couch verification of ion‐beam treatment plans. The aim of this work is to introduce and evaluate a method for quantitative water‐equivalent thickness (WET) measurements for a specific helium‐ion imaging system for WETs that are relevant for imaging thicker body parts in the future. Methods: Helium‐beam radiographs (αRads) are measured at the Heidelberg Ion‐beam Therapy Center with an initial beam energy of 239.5 MeV/u. An imaging system based on three pairs of thin silicon pixel detectors is used for ion path reconstruction and measuring the energy deposition (d E ) of each particle behind the object to be imaged. The d E behind homogeneous plastic blocks is related to their well‐known WETs between 280.6 and 312.6 mm with a calibration curve that is created by a fit to measured data points. The quality of the quantitative WET measurements is determined by the uncertainty of the measured WET of a single ion (single‐ion WET precision) and the deviation of a measured WET value to the well‐known WET (WET accuracy). Subsequently, the fitted calibration curve is applied to an energy deposition radiograph of a phantom with a complex geometry. The spatial resolution (modulation transfer function at 10 % —MTF10% ) and WET accuracy (mean absolute percentage difference—MAPD) of the WET map are determined. Results: In the optimal imaging WET‐range from ∼280 to 300 mm, the fitted calibration curve reached a mean single‐ion WET precision of 1.55 ± ± 0.00%. Applying the calibration to an ion radiograph (iRad) of a more complex WET distribution, the spatial resolution was determined to be MTF10% = 0.49 ± ± 0.03 lp/mm and the WET accuracy was assessed as MAPD to 0.21 %. Conclusions: Using a beam energy of 239.5 MeV/u and the proposed calibration procedure, quantitative αRads of WETs between ∼280 and 300 mm can be measured and show high potential for clinical use. The proposed approach with the resulting image qualities encourages further investigation toward the clinical application of helium‐beam radiography.